2023
DOI: 10.3390/buildings13061427
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Building Energy Modeling Using Prototype Model and Automatic Model Calibration for Retrofit Analysis with Uncertainty

Abstract: Building performance simulation can be used for retrofit analysis. However, it is time-consuming to create building energy models for existing buildings. This paper presented and implemented a rapid building energy modeling method for existing buildings by using prototype models and automatic model calibration for retrofit analysis with uncertainty. A shopping mall building located in Changsha, China, was selected as a case study to demonstrate the rapid modeling method. First, a toolkit named AutoBPS-Param wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(35 reference statements)
0
0
0
Order By: Relevance
“…Four function models exist in Au-toBPS: AutoBPS-GEO, AutoBPS-OSS, AutoBPS-RM, and AutoBPS-PV. Wei et al [30] showed AutoBPS-Param to present a rapid model for an existing shopping mall. Though Wei et al [30] have shown the rapid establishment progress for a shopping mall using AutoBPS-Param, this paper further develops the AutoBPS-Param for complex different building types with pre-defined parameters.…”
Section: Model Establishment Via Autobps-parammentioning
confidence: 99%
“…Four function models exist in Au-toBPS: AutoBPS-GEO, AutoBPS-OSS, AutoBPS-RM, and AutoBPS-PV. Wei et al [30] showed AutoBPS-Param to present a rapid model for an existing shopping mall. Though Wei et al [30] have shown the rapid establishment progress for a shopping mall using AutoBPS-Param, this paper further develops the AutoBPS-Param for complex different building types with pre-defined parameters.…”
Section: Model Establishment Via Autobps-parammentioning
confidence: 99%
“…Figure 2 presents the building geometry of the baseline model illustrating the baseline shopping mall model, which serves as a prototype and is generated using AutoBPS. The parameters of the baseline model are modified through calibration and modeling based on empirical data collected from a specific commercial building in Changsha [47]. This procedure is supported by collecting monthly actual energy consumption data of the commercial buildings, along with basic building parameters like the building envelope structure.…”
Section: Baseline Model Of the Shopping Mallmentioning
confidence: 99%
“…This procedure is supported by collecting monthly actual energy consumption data of the commercial buildings, along with basic building parameters like the building envelope structure. Subsequently, this data is input into the urban building modeling tool, Au The parameters of the baseline model are modified through calibration and modeling based on empirical data collected from a specific commercial building in Changsha [47]. This procedure is supported by collecting monthly actual energy consumption data of the commercial buildings, along with basic building parameters like the building envelope structure.…”
Section: Baseline Model Of the Shopping Mallmentioning
confidence: 99%